2011
DOI: 10.3390/cancers3044281
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Investigation of the Role of Interleukin-4 and Interleukin-13 in the Evolution of Prostate Cancer

Abstract: Prostate cancer is the most common cancer in men, both in the USA and Europe. Although incurable, metastatic disease can often be controlled for years with anti-androgen therapy. Once the disease becomes castrate resistant, the median survival is 18 months. There is growing evidence that the immune system, and in particular cytokines, play an important role in prostate cancer immunosurveillance and progression. Here, we have undertaken a clinical investigation of the role of two closely related cytokines, IL-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 47 publications
2
26
0
1
Order By: Relevance
“…44 Analysis of benign and malignant prostate tissue demonstrates that the source of IL-4 is epithelial cells rather than infiltrating leukocytes. 45 It is generally recognized that TAMs may polarize to the M2 macrophage phenotype stimulated by IL-4, IL-10, and IL-13. 5 In our study, co-culture experiments were performed with cell co-culture inserts, which allowed no direct contact between PCa cells and macrophages, so that only soluble mediators were able to affect cellular activity.…”
Section: Discussionmentioning
confidence: 99%
“…44 Analysis of benign and malignant prostate tissue demonstrates that the source of IL-4 is epithelial cells rather than infiltrating leukocytes. 45 It is generally recognized that TAMs may polarize to the M2 macrophage phenotype stimulated by IL-4, IL-10, and IL-13. 5 In our study, co-culture experiments were performed with cell co-culture inserts, which allowed no direct contact between PCa cells and macrophages, so that only soluble mediators were able to affect cellular activity.…”
Section: Discussionmentioning
confidence: 99%
“…Goldstein and coworkers, 2011, showed a different immunoreactivity of IL-4 in prostatic cells of BPH and prostatic cancer. Analysis of benign and malignant prostate tissues demonstrated that the source of IL-4 is the epithelial cells rather than infiltrating leukocyte [24]. In the normal group we observed a glandular epithelium with cellular monolayer and an IL-4 signal in the basal area, while in the WOT and placebo groups we observed hyperplasic and hypertrophic regions and a poor IL-4 expression in the luminal region (Figure 5(a)).…”
Section: Resultsmentioning
confidence: 95%
“…Consistent with the present report, our previous study investigating the role of IL-17 in the context of CD4+ T-cell responses to TAAs documented a negative impact ofIL-17-producing T-cells in late-stage melanoma [ 20 ]. There are several other cytokines such as IL-4 and IL-13 that are known to have a negative impact on survival [ 31 , 32 ] and which would have been interesting to examine here, especially as we previously found that IL 4 was relevant in melanoma. IL-13 is known to regulate cancer invasion and metastasis in different cancers [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%